2012
DOI: 10.1590/s0100-40422012001100025
|View full text |Cite
|
Sign up to set email alerts
|

Anti-trypanosomal activity of 1,2,3,4,6-penta-O-galloyl-β -D-glucose isolated from Plectranthus barbatus Andrews (Lamiaceae)

Abstract: Recebido em 25/5/12; aceito em 17/9/12; publicado na web em 9/11/12MeOH extract from the leaves of Plectranthus barbatus Andrews (Lamiaceae), showed in vitro anti-trypanosomal activity. The bioassay-guided fractionation resulted in the isolation of a gallic acid derivative, identified as 1,2,3,4,6-penta-O-galloyl-b-D-glucose (PGG), after thorough NMR and MS spectral analysis. Finally, this compound was tested against trypomastigote forms of T. cruzi and displayed an EC 50 value of 67 µM, at least 6.6-fold more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Additionally, although Plectranthus barbatus was only indicated for digestive problems by participants, a review of the species [69] mentions pharmacological actions, including hypotensive, positive-inotropic actions, cardiovascular, bronchodilator, activation of adelilatocyclase, inhibition of platelet aggregation (anti-metastasis), antitumor, anti-inflammatory and anti-nociceptive. Another study [70] identified in vitro anti-transpanosomal activity and a brief literature review revealed it has antioxidant, antimicrobial, antifungal, and anti-acetylcholinesterase activities. Furthermore, another study [71] referred to this species’ potential antimalarial action.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, although Plectranthus barbatus was only indicated for digestive problems by participants, a review of the species [69] mentions pharmacological actions, including hypotensive, positive-inotropic actions, cardiovascular, bronchodilator, activation of adelilatocyclase, inhibition of platelet aggregation (anti-metastasis), antitumor, anti-inflammatory and anti-nociceptive. Another study [70] identified in vitro anti-transpanosomal activity and a brief literature review revealed it has antioxidant, antimicrobial, antifungal, and anti-acetylcholinesterase activities. Furthermore, another study [71] referred to this species’ potential antimalarial action.…”
Section: Resultsmentioning
confidence: 99%
“…1, 2, 3, 4, 6-Penta- O -galloyl- β -D-glucoside ( 1 ): maple powder; 1 H and 13 C NMR data matched literature values [ 14 ].…”
Section: Methodsmentioning
confidence: 53%
“…Based on the activity results of extract and all fractions, dichloromethane, ethyl acetate, and n -butanol fractions were applied to further isolation and purification by chromotography on Sephadex LH-20 column, silica gel column, ODS, and preparative TLC, as well as semipreparative HPLC, et al Finally, 17 compounds were obtained. Their structures were identified as 1, 2, 3, 4, 6-penta- O -galloyl- β -D-glucoside ( 1 ) [ 14 ], 1, 2, 3, 4, 6-penta- O -galloyl- α -D-glucoside ( 2 ) [ 15 ], 1, 2, 3, 6-tetra- O -galloyl- β -D-glucoside ( 3 ) [ 16 ], 1- O -(3, 4, 5-trihydroxybenzoyl)- β -D-glucoside ( 4 ) [ 17 ], methyl galate ( 5 ) [ 18 ], gallic acid ( 6 ) [ 39 ], 3,4-dihydroxybenzoic acid ( 7 ) [ 19 ], 4-hydroxybenzoic acid ( 8 ) [ 20 ], 1-glycerol gallate ( 9 ) [ 21 ], ethyl gallate ( 10 ) (H. [ 22 ]), ferulic acid ( 11 ) [ 23 ], caffeic acid ( 12 ) [ 24 ], quercetin ( 13 ) [ 25 ], genistein ( 14 ) [ 26 ], gallocatechin ( 15 ) [ 27 ], epicatechin ( 16 ) (M. [ 28 ]), and hexyl- β -D-glucoside ( 17 ) [ 29 ] by comparing their NMR spectroscopic data with data reported in the above references. Compounds 2 , 9 , 15 , and 17 were isolated from the genus Mangifera for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports highlighted the in vitro efficacy of some flavonoid compounds against T. brucei [19]. Moreover, penta-O-galloyl-β-D-glucose was revealed to have in vitro anti-trypanosomal activity [48]. Furthermore, gallic acid was cited to exert its effect on T. brucei via iron chelation that caused structural and morphological changes and stopping the cell cycle [49].…”
Section: Docking Study For Anti-trypanosomal Activitymentioning
confidence: 99%